2021
DOI: 10.1080/17449480.2021.1933113
|View full text |Cite
|
Sign up to set email alerts
|

From voluntary to mandatory non-financial disclosure following Directive 2014/95/EU: an Italian case study

Abstract: This study investigates the non-financial disclosure in an Italian banking group following Directive 2014/95/EU over a period of eight years, from its voluntary (2013)(2014)(2015)(2016)(2017) to mandatory (2018)(2019)(2020) implementation. The paper relies both on primary and secondary data sources. It first adopts a content analysis on non-financial reports while considering other relevant available material. Second, the study relies upon semi-structured interviews and seminars to gather primary data. The ana… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
56
2
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 52 publications
(61 citation statements)
references
References 50 publications
2
56
2
1
Order By: Relevance
“…Most of the Spanish studies aimed to explore the mandatory reporting of NFI by analysing the reporting behaviour of Spanish companies With reference to the Italian case, most of the studies compared NFI before and after the decree, showing, on the one hand, an increase in the quality of disclosure (Leopizzi et al 2019;Mion and Loza Adaui 2019;Caputo et al 2020;Nicolò et al 2021) and, on the other hand, a general reduction in the number of sustainability indicators disclosed by Italian companies (Loprevite et al 2020;Tarquinio et al 2020). On the contrary, Korca et al (2021) found a significant increase in the quantity but not in the quality of NFI. Other authors, instead, did not find a decisive influence of the Directive on disclosure levels (Carungu et al 2020;Nicolò et al 2020).…”
Section: Literature Reviewmentioning
confidence: 63%
“…Most of the Spanish studies aimed to explore the mandatory reporting of NFI by analysing the reporting behaviour of Spanish companies With reference to the Italian case, most of the studies compared NFI before and after the decree, showing, on the one hand, an increase in the quality of disclosure (Leopizzi et al 2019;Mion and Loza Adaui 2019;Caputo et al 2020;Nicolò et al 2021) and, on the other hand, a general reduction in the number of sustainability indicators disclosed by Italian companies (Loprevite et al 2020;Tarquinio et al 2020). On the contrary, Korca et al (2021) found a significant increase in the quantity but not in the quality of NFI. Other authors, instead, did not find a decisive influence of the Directive on disclosure levels (Carungu et al 2020;Nicolò et al 2020).…”
Section: Literature Reviewmentioning
confidence: 63%
“…Additionally, our results add to previous studies reporting that the NFRD has influenced firms’ coverage and disclosure levels across sustainability topics. Korca et al (2021) found that the amount of information published by the Italian banking group analyzed in their case study increased for all the matters required by the Italian transposition, yet only the quality of social and employee disclosures improved. Carini et al (2021) also reported that the NFRD shaped companies’ coverage of sustainability matters.…”
Section: Discussionmentioning
confidence: 92%
“…Carini et al (2021) performed a case study of an oil and gas company, showing that the coverage of environmental topics in its reports increased after the enactment of the Italian transposition. By contrast, the case study of Korca et al (2021) of a banking firm shows that the impact of the NFRD differs depending on the reported topics. They found that the quantity of information increased for all sustainability topics, while its quality only improved for social and employee-related disclosures.…”
Section: Literature Reviewmentioning
confidence: 85%
See 1 more Smart Citation
“…In fact, despite the positive externalities related to the introduction of specific rules about non-financial reporting, many academics have reiterated the existence of different effects related to the transposition of the Directive 2014/95/EU. In particular, the theoretical debate distinguishes between the effects on latecomers and early adopters (Korca et al , 2021). On the one hand, the Directive 2014/95/EU can become a disruptive innovation for latecomers who do not have any experience in sustainability reporting (Caputo et al , 2019; Doni et al , 2019).…”
Section: Theoretical Frameworkmentioning
confidence: 99%